Insulin resistance/hyperinsulinemia: an important cardiovascular risk factor that has long been underestimated - Fazio, Serafino; Mercurio, Valentina; Tibullo, Loredana; Fazio, Valeria; Affuso, Flora (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular mortality is still excessively high, despite the considerable progress made in the prevention and treatment of cardiovascular diseases. Although many cardiovascular risk factors (such as arterial hypertension, hypercholesterolemia, diabetes, etc.), identified in the general population, are being promptly treated, to date little consideration is given to a cardiovascular risk factor which we believe has largely demonstrated in the scientific literature of the last three decades that, if neglected, can produce a series of relevant negative effects on the cardiovascular system: insulin resistance (IR)/hyperinsulinemia (Hyperins). This risk factor is still not sufficently sought in the general population and, consequently, is not treated promptly, as it should be, to avoid its negative impact on the cardiovascular system. IR's prevalence is constantly growing worldwide, and it is estimated to have reached a prevalence of 51% of the general population in developed and developing countries, and Hyperins is a constant and strong feature of IR. This article aims to stimulate the scientific community towards IR/Hyperins as relevant cardiovascular risk factor, since it is still neglected. The scientific literature analyzed and used to for this article was found on PubMed, Scopus, Science Direct, etc, using the following keywords: insulin, insulin signaling, insulin resistance, hyperinsulinemia, cardiovascular risk factors, cardiovascular system, cardiovascular diseases. We selected studies that explored the association between IR/Hyperins and the cardiovascular system, and those that discussed the possibilities of screening and treatment of IR/Hyperins.